Serious infestation of Rhipidothrips brunneus Williams (Thysanoptera Aeolothripidae) on wheat in Tuscany (Bollettino di zoologia agraria e bachicoltura, 2024)
The Authors report an unusual pullulation of Rhipidothrips brunneus Williams(Thysanoptera Aeolothripidae) harmful to seed crops of common and durum wheatin Agro Pisano (Tuscany, Central Italy). We have observed a mortality of seedlings,whilst older plants (2-3 leaves) showed severe alterations of the epigeanpart and were less vigorous. About 30 hectares of totally destroyed crop, had tobe sown again. Possible pest management measures for organic farming and IPMstrategies are being discussed.
Keywords: Rhipidothrips brunneus; Tuscany; durum wheat; common wheat; damage; IPM